SOCIALIZATION THROUGH SPORT. EFFECTS OF PHYSICAL EDUCATION AND SPORT - Marian Dionisie Turcu; Raul Todor (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Diversity effects sport and physical activity is found in diverse spheres of influence it. Addressed key issues relate to physical, psychic unity relationship, essential in the development of individual personality, the importance of building a beautiful body motricity and maintain his health, the role of sport and physical activity in human socialization by developing qualities recognized important in society and can be transferred to other social spheres and the impact these effects on different population groups in sport and exercise.